Soil Fungal Diversity, Community Structure, and Network Stability in the Southwestern Tibetan Plateau - Shiqi Zhang; Zhenjiao Cao; Siyi Liu; Zhipeng Hao; Xin Zhang; Guoxin Sun; Yuan Ge; Limei Zhang; Baodong Chen (Journal of Fungi)
Despite substantial research on how environmental factors affect fungal diversity, the mechanisms shaping regional-scale diversity patterns remain poorly understood. This study employed ITS high-throughput sequencing to evaluate soil fungal diversity, community composition, and co-occurrence networks across alpine meadows, desert steppes, and alpine shrublands in the southwestern Tibetan Plateau. We found significantly higher fungal α-diversity in alpine meadows and desert steppes than in alpine shrublands. Random forest and CAP analyses identified the mean annual temperature (MAT) and normalized difference vegetation index (NDVI) as major ecological drivers. Mantel tests revealed that soil physicochemical properties explained more variation than climate, indicating an indirect climatic influence via soil characteristics. Distance–decay relationships suggested that environmental heterogeneity and species interactions drive community isolation. Structural equation modeling confirmed that the MAT and NDVI regulate soil pH and carbon/nitrogen availability, thereby influencing fungal richness. The highly modular fungal co-occurrence network depended on key nodes for connectivity. Vegetation coverage correlated positively with network structure, while soil pH strongly affected network stability. Spatial heterogeneity constrained stability and diversity through resource distribution and niche segregation, whereas stable networks concentrated resources among dominant species. These findings enhance our understanding of fungal assemblage processes at a regional scale, providing a scientific basis for the management of soil fungal resources in plateau ecosystems.